Length distinguishes the significance of syllables in mouse ultrasonic communication - Lee, Gyu-Hwan; Lee, Kangmin; Lee, Jaehyun; Choi, Ji Hyun (Neuroscience 2024, 2024)
Although more and more studies suggest important role of ultrasonic vocalization (USV) in mouse social communication, it has been unclear which feature of USV syllables acts as a distinctive feature that differentiate the significance of syllables in their communication. Previously defined syllable classes failed in showing clear behavioral relevance. In search of a syllable property that provides a criteria for behaviorally, physically and neurologically meaningful division of mouse social signals, current study took a multimodal approach where courtship behavior was monitored while measuring breathing and brain signals. Over 20,000 syllables were detected from 18 male-female encounters. First looking at the distributions of syllable acoustic properties, syllable length exhibited a bimodal distribution, while other distributions were unimodal. Dimensionality reduction analyses showed that syllables are separable into two groups when their position and spectrotemporal modulation within the breathing cycle were taken into account. We therefore classified the detected syllables as either ‘long’ or ‘short.’ Physiologically, only syllables in the long class were found to linearly extend the length of exhalation, suggesting active suppression of inhalation during the production of long syllables. In terms of behavioral context, long syllables prominently occurred during close, face-to-face interaction. In order to monitor real-time brain activity during social communication, the CBRAIN telemetry system was utilized to measure the LFP activities from nucleus accumbens (NAc) of male and female mice. Frequency of beta (24？32 Hz) bursts in both sexes highly increased during social interaction, especially during vocalization. In addition, beta burst activity was positively correlated with the occurrence rate of long syllables. Finally, information theoretic measures suggest increased information flow between male and female LFP signals during vocal communication, followed by behavioral consequences such as increased probability of approaching and mating. This study suggests that mice are able to employ distinct vocal units, distinguished by their length, to signify social intent. Furthermore, ultrasonic communication is found to facilitate fast information transmission between the brains of social partners.